2017
DOI: 10.7863/ultra.16.02005
|View full text |Cite
|
Sign up to set email alerts
|

Blood‐Brain Barrier Closure Time After Controlled Ultrasound‐Induced Opening Is Independent of Opening Volume

Abstract: Objectives Microbubble-mediated focused ultrasound (US) opening of the blood-brain barrier (BBB) has shown promising results for the treatment of brain tumors and conditions such as Alzheimer disease. Practical clinical implementation of focused US treatments would aim to treat a substantial portion of the brain; thus, the safety of opening large volumes must be investigated. This study investigated whether the opened volume affects the time for the BBB to be restored after treatment. Methods Sprague Dawley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 37 publications
4
55
0
Order By: Relevance
“…The time necessary for the barrier to be fully restored has been found proportionally related to the opening volume assuming the induction of a single opening . The decoupling of this dependence has been achieved by substituting large openings with small multifoci openings decreasing the necessary time for the barrier to be restored . Longitudinal studies on rodents and primates have shown that repeated ultrasound‐induced BBB opening in the absence of vascular damage is a transient and reversible application .…”
Section: The Bbb Opening With Fusmentioning
confidence: 99%
See 1 more Smart Citation
“…The time necessary for the barrier to be fully restored has been found proportionally related to the opening volume assuming the induction of a single opening . The decoupling of this dependence has been achieved by substituting large openings with small multifoci openings decreasing the necessary time for the barrier to be restored . Longitudinal studies on rodents and primates have shown that repeated ultrasound‐induced BBB opening in the absence of vascular damage is a transient and reversible application .…”
Section: The Bbb Opening With Fusmentioning
confidence: 99%
“…24 The decoupling of this dependence has been achieved by substituting large openings with small multifoci openings decreasing the necessary time for the barrier to be restored. 25,26 Longitudinal studies on rodents and primates have shown that repeated ultrasound-induced BBB opening in the absence of vascular damage is a transient and reversible application. 27,28 Restoration of the barrier was not only macroscopically evaluated by magnetic resonance imaging but also neurologically by visual, cognitive, motivational, and motor function behavioral testing.…”
Section: The Bbbmentioning
confidence: 99%
“…Lastly, a completely separate and additional advantage of such LCM/ND lipid nanoemulsion(s), as a component of this combination therapeutic, stems from the characteristic lipid-coated microbubble subpopulation (D'Arrigo 2011) existing in this nanoemulsion type. Specifically, such preformed (lipidstabilized) microbubbles are well known to substantially reduce the acoustic power levels needed for accomplishing temporary noninvasive (transcranial) ultrasound treatment Alonso et al 2010;Alonso et al 2011;Aslund et al 2017;Bing et al 2014;D'Arrigo 2015;Delalande et al 2013;Goliaei et al 2015;Kotopoulis et al 2013;Kotopoulis et al 2014;Lammers et al 2015;Marquet et al 2011;Meairs 2015;Meng et al 2017;Miller and O'Callaghan 2017), or sonoporation (Aubry et al 2016;Bouakaz et al 2016;Burgess and Hynynen 2016;Castle and Feinstein 2016;Delalande et al 2015;Horodyckid et al 2016;O'Reilly et al 2017;Paefgen et al 2015;Qin et al 2016;Sennoga et al 2016), if additionally desired for the Alzheimer's patient.…”
Section: Resultsmentioning
confidence: 99%
“…O’Reilly et al investigated the time taken for the BBB to close and the opening volume on the time scale of closure after focused US exposure; no significant differences were detected on MRI between large- and small-volume sonications, suggesting that safe BBB opening can be achieved by US combined with microbubbles 79. Lin et al demonstrated that the BBB can be successfully opened by US-triggered microbubble destruction and thus the delivery of exogenous substances can be significantly improved, although the specific mechanisms are still unclear 80.…”
Section: Immunotherapy Assisted By Ummdmentioning
confidence: 99%